Translation of Ambiguous Words by Translation Trainees - Filiz Mergen; Nihal Yetkin-Karakoç (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
Ambiguity has attracted the attention of researchers from many disciplines. With the aim of providing a perspective from translation, this psycholinguistic study investigated ambiguity in the translation performance of late bilinguals from English (L2) into Turkish (L1). We employed an oral translation task in which the participants (N= 51) translated 30 ambiguous words, (polysemes and homonyms) in contextualized sentences. First, we investigated whether word frequency affects the participants’ translation accuracy. We found no significant difference between high and low frequency words, which is attributable to the proficiency of the participants, and the facilitating role of sentential context. Secondly, we aimed to explore whether the nature of the ambiguous words made any difference to the participants’ translation performance. The results showed that polysemous words were translated with greater accuracy than homonymous words, in line with the data in the literature regarding the differences in the representation and processing of polysemy and homonymy.